Determinants of performance in Indonesian banking: a cross-sectional and dynamic panel data analysis - Sarita, Buyung; Zandi Pour Joopari, GholamReza; Shahabi, Alireza (Social Sciences Research Society, 2012)
This paper examines determinants of bank performance in Indonesia for the period of 1994-1999. It was pooled cross-sectional time series and dynamic panel data models. This research incorporates the traditional Structure-Conduct- Performance (SCP) and Relative Efficiency (RE) hypotheses. The estimation results show that bank performance industry is competitive, and implies that market structure in Indonesian banking sector is nearly perfect competition. However, no evidence has been found in this study in support of the traditional SCP, while RE is otherwise. The negative relationship between loans to business groups and bank performance, which is likely due to the high loans provided to them, thus supporting the moral hazard hypothesis. The negative relationship between market share loan and return on assets, the negative relationship between debt-to-total assets and bank performance is likely because of the high level of debt. The negative relationship between debt-to-total assets and bank performance in a scenario of high interest rates indicates that banks acted responsibly by paying high interest charges prevailing at that time. This also results in the negative relationship between capital adequacy ratio and bank performance.